PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV.B SD NEGERI 62 PEKANBARU - Dian Anggraini; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This research was aimed to increase learning proces and student achievement of science lesson V.C grade years of 2014 / 2015. Subject of this research is student IV.B grade of state elementary school 62 Pekanbaru which is total 30 students, consisted of 21 girls and 14 boys. This was a classroom research which has two cycles.the data shown either learning proces icreased. The basic score of daily examination as 12,04% which 25 students passed and 10 students failed. The ending of daily examination was as 71,43%. The second daily examination alsos increased from basic score as 21,44% which 32 students passed and 3 students failed. The ending of second daily examination was 94,43%. Based on the expalanation above it can be concluded that the imlpementation learning cooperatif type think pair share (TPS) increased students’ achievement in science lesson of students IV.B grade of state elementary school 62 Pekanbaru.Keywords : Cooperatif Think Pair Share (TPS), Students Achievement The Result Of Science Studies